Pengaruh Pelatihan Dan Pengembangan Terhadap Karir Pegawai Dengan Modal Sosial Sebagai Variabel Mediasi (Studi Pada Dinas Perhubungan Kota Malang) - Rahayu, Fatikha; Pardiman, Pardiman; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aim to examines the effect of training and development on employee career advancement with social capital serving as a mediating variable at the Malang City Transportation Office. A quantitative approach with a confirmatory research design was employed. Primary data were collected through questionnaires administered to 58 civil servants selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling with the Partial Least Square (SEM-PLS) technique via SmartPLS software. The results reveal that training and development have a positive and significant effect on employee career advancement as well as on social capital. Moreover, social capital exerts a positive influence on employee career outcomes and partially mediates the relationship between training and development and career advancement. These findings indicate that the effectiveness of training initiatives is not solely determined by improvements in individual competencies, but also by the formation of professional networks, trust, and collaborative social relationships within the organization. Consequently, strengthening social capital constitutes a strategic mechanism for enhancing the impact of training programs and supporting sustainable career development among public sector employees. Keywords: training and development, social capital, employee career..